Reconciling at‐a‐Station and at‐Many‐Stations Hydraulic Geometry Through River‐Wide Geomorphology - C. B. Brinkerhoff; C. J. Gleason; D. W. Ostendorf (Geophysical Research Letters)
Abstract At‐many‐stations hydraulic geometry (AMHG), while useful for estimating river discharge from satellite data, remains empirical and has yet to be reconciled with the at‐a‐station hydraulic geometry (AHG) from which it was originally derived. Here we present evidence, using United States Geological Survey field measurements of channel hydraulics for 155 rivers, that AMHG can be hydraulically and geomorphically reconciled with AHG. Our results indicate that AMHG is rightly understood as an expression of a river‐wide model of hydraulics driven by changes in slope imposed upon AHG physics. The explanatory power of AHG and this river‐wide model combine to determine whether AMHG exists: if both AHG and the river‐wide model adequately describe hydraulics, then we show that AMHG is a necessary mathematical consequence of these two phenomena. We also orient these findings in the context of river discharge estimation and other applications.